2021
DOI: 10.3389/fneur.2021.663400
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Conditioning May Improve Disability and Cognition After Acute Ischemic Stroke: A Pilot Randomized Clinical Trial

Abstract: Background and Aim: Remote ischemic conditioning is a procedure purported to reduce the ischemic injury of an organ. This study aimed to explore the efficiency and safety of remote ischemic conditioning in patients with acute ischemic stroke. We hypothesized that remote ischemic conditioning administered from the first day of hospital admission would improve the infarct volume and clinical outcome at 180 days.Material and Methods: We performed a unicentric double-blind randomized controlled trial. We included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Poalelungi et al ( 33 ) noted in the study that the reason for the difference not being statistically significant could be that the intervention had already been administered to the patients at the time of the baseline measurement, when RIPostC had already had an effect on the patients' cerebral infarct volumes. Further, in that study the baseline measurement was performed after the intervention had began; and another reason could be that the sample size was not large enough ( n = 40).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Poalelungi et al ( 33 ) noted in the study that the reason for the difference not being statistically significant could be that the intervention had already been administered to the patients at the time of the baseline measurement, when RIPostC had already had an effect on the patients' cerebral infarct volumes. Further, in that study the baseline measurement was performed after the intervention had began; and another reason could be that the sample size was not large enough ( n = 40).…”
Section: Resultsmentioning
confidence: 96%
“…A total of 12 eligible studies were included ( 22 33 ), all of which included patients with ischemic cerebrovascular disease. Eleven studies were analyzed quantitatively, and one study ( 33 ) was analyzed only qualitatively because the data could not be accurately extracted. A total of 713 patients were included, 353 in the trial group and 360 in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poalelungi et al evaluated the effect of RIC applied in first 5 days after onset of patients, and results suggested that RIC partly improved disability and cognition without statistical difference. 91 Similarly, there are no significant improvements in infarct size or clinical outcome in patients who receive RIC for 4 days…”
Section: Challeng E S and Future D Irec Ti On S For The S Tudy Of Ric...mentioning
confidence: 99%
“…The results of these studies emphasized the neuroprotection role of short‐term RIC at the beginning of stroke onset, but the effect of chronic RIC application on stroke patients remain unclear. Poalelungi et al evaluated the effect of RIC applied in first 5 days after onset of patients, and results suggested that RIC partly improved disability and cognition without statistical difference 91 . Similarly, there are no significant improvements in infarct size or clinical outcome in patients who receive RIC for 4 days after stroke 92 .…”
Section: Challenges and Future Directions For The Study Of Ric In Pos...mentioning
confidence: 99%